Arctic Test Season, 1962-63 - ARMY ARCTIC TEST CENTER FORT GREELY AK (1963)
U. S. Army Arctic test board report April/May 1962-memorandum. Purpose of this Memorandum Report is to highlight the test activities of the US Army Arctic Test Board, to report on specific problems of supply and maintenance of test and support items, and to furnish general information on the performance of equipment under test. Attempt will be made to acquire and present test information in sufficient detail to enable project engineers and other interested persons to evaluate the progress of each test.